OPTIMASI PROSES PEMBUATAN LIPSTIK DENGAN PENAMBAHAN BERBAGAI KONSENTRASI MALAM LEBAH - Oscar Perdanakusuma dan Zakiah Wulandari (Jurnal Teknologi Industri Pertanian, 2005)
ABSTRACTBeeswax concentrations as much as 15%, 25%, 35% and 45% produced lipstick with hardness and melting point fulfilling the standard.  Lipstick making process used heating temperature at 850C and pouring temperature into the mould at 700C.  The needed average time for mixing were 14,25 minutes.  Increased beeswax concentration that substitute castor oil in lipstick making formula will result lipstick with hardness and melting point which to mount.  Crack level in moulting lipstick leveled up with more beeswax concentration used in formulation.  Texture, shine and fragnace have tight connect with beeswax concentrations in lipstick.  Mounted beeswax concentration, resulted lipstick with ruder texture, gloomer shine and more fragnaceless.  Rub effect less connect with beeswax concentration.  Mounted beeswax concentration, lipstick tendency less attached.  Colour less tight connect with beeswax concentration.  The best lipstick quality is lipstick with 25% beeswax concentration.Key words : lipstick, beeswax, castor oil